The study of the good polishing method for polymer SU-8 waveguide - Ab-Rahman, Mohammad Syuhaimi; Ab-Aziz, Fazlinda; Mohd Arif, Noor Azie Azura; Zan, Saiful Dzulkefly; Mustaza, Seri Mastura; Ehsan, Abang Anuar; Shaari, Sahbudin (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
This research focused on polish characteristic of polymer based waveguides. The aim of the research was to show how polishing parameters affect the cut length of the end surface of SU-8 polymer on silicon and to detemine the best parameters for polishing SU-8 polymer. Then, four samples were used for characterizing the polishing of polymer. Each sample was polished with the same rotation and sandpaper size but with different rotational speed. The experiment result shows that the best rotational speed for polishing polymer SU-8 sample on silicon is 200 rpm.
Optica Applicata, Vol. 39, 2009, nr 3, s. 459-465
Keywords: optyka; waveguides polishing; SU-8 polymer; rotational speed; sandpaper; silicon; cut off length